(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Diagnostic Techniques Of Indian Medicine System Takes Its Root From Understanding And Analyzing The Three Radial Pulses. Pulse Or Nadi (Sanskrit Term) Is A Vital Movement Of Energy, That Is, Life Which Advances Along The Fine Medium Throughout The Human Body That Helps The Physician To Feel And Understand The Flow Of Blood All Along From The Heart. Nadipariksha Is An Ancient Ayurvedic Technique Of Diagnosis Through The Pulse Or Nadi. It Is A Powerful Way Of Diagnosing Physical, Mental And Emotional Imbalances As Well As Diseases. This Non-Invasive Technology Aids In Reaching The Root Cause Of Bodily Imbalances And Health Disorders In Addition To Addressing The Symptoms.